A Blockchain Voting System Based on the Feedback Mechanism and Wilson Score - Xiaoyu Ma; Jiting Zhou; Xiumei Yang; Guangyuan Liu (Information, 2020)
A blockchain voting system based on the feedback mechanism and Wilson score is proposed to solve the problem of the malicious votes behavior. Firstly, the relatively accurate supporting rate and ranking for candidates are obtained using the Wilson score. Secondly, different feedback coefficients are calculated according to the above parameters. Finally, the account points are adjusted according to the feedback coefficients. The feedback mechanism is designed in the voting smart contract, and the smart contract is deployed on the blockchain to ensure the enforcement of the feedback mechanism. A fully functional smart contract is designed and briefly verified in this paper. The experiment is conducted under the K-out-of-L type of weighted voting. Experimental results show that the Wilson score can accurately modify the candidates’ supporting rates, and the feedback mechanism can effectively suppress malicious votes.